Use of negative pressure wound therapy to help facilitate limb preservation - Armstrong, David G (Int Wound J, 2012)
Because of changes in demography, non‐communicable diseases cause more deaths worldwide than infectious disease for the first time in history. One of the most prevalent of these maladies is diabetes mellitus, which resulted in 4·6 million deaths in 2011. There will be approximately 552 million people with diabetes worldwide by 2030. For these patients, one of the most common severe complications will be a foot wound. Patients with diabetes have at least a 25% lifetime risk of developing a foot ulcer. Many of these infections go on to amputation. Those patients have a 50% mortality rate in the 5 years following the initial amputation. Indeed, these problems are costly as well. In 2010, spending on diabetes was estimated to account for 11·6% of the total health care expenditure in the world. This review merges scientific evidence with expert experience to show the role of negative pressure wound therapy using reticulated open cell foam (V.A.C.® Therapy, KCI USA, Inc., San Antonio, TX) in limb preservation.